Isolated Rosai-Dorfman disease of the spine: A systematic literature review - Slouma, Maroua; Bouzid, Sirine; Tlili, Karima; Yedaes, Dahmani; Radhwen, Khaled; Gharsallah, Imen (Clinical neurology and neurosurgery, 2024)
Rosai-Dorfman disease (RDD) is a rare non–Langerhans cell histiocytosis involving the central nervous system in 5% of cases. Spinal location occurs in less than 1% of extranodal RDD and can be responsible for neurological manifestations. We present a systematic review of cases of isolated spinal RDD. We also report a new case of isolated spinal RDD revealed by spinal cord compression. The systematic review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guideline using the MEDLINE and SCOPUS databases and included case reports and case series describing isolated RDD of the spine. There were 53 patients with isolated spinal RDD (including our case). The mean age was 35.85±16.48 years. Neurological deficit was the most frequent clinical presentation (89%). RDD lesions were mainly located in the thoracic spine (51%), then the cervical spine (32%). The lesion was reported to be extradural (57%), intradural extramedullary (26%), intramedullary (7%), and in the vertebral body (10%). Histological examination showed emperipolesis in 73%. Histocytes were positive for S-100 protein in 83%. Treatment was based on surgery 96%), radiotherapy, chemotherapy, and adjunctive steroid therapy were indicated in four, one, and eight cases. After a mean follow-up period of 14.84±13.00 months, recurrence of RDD was noted in 15%. Spinal RDD is a rare condition, requiring meticulous histological examination for accurate diagnosis. Complete surgical resection is the treatment of choice. Adjuvant chemotherapy and radiotherapy can also be indicated in patients demonstrating partial improvement following surgery. •Isolated Rosai-Dorfman disease of the spine is a rare entity.•Diagnosing isolated spinal RDD can be challenging due to the absence of common RDD manifestations.•Surgical resection of the lesion is crucial for both diagnostic and treatment purposes.